MORBIDITY AND MORTALITY IN BREAST CONSERVATION SURGERY IN EARLY CARCINOMA BREAST: Morbidity and Mortality in Breast Conservation Surgery - Kayani, Muhammad Shahbaz Bakht; Zaheer, Muhammad; Ashraf, Naeem; Malik, Asad Mahmud (Pakistan Armed Forces Medical Journal, 2008)
Objective: To study the mortality and morbidity after breast conservation surgery (BCS) in patients with early breast cancer and comparison with local and international literature.Design: An Interventional descriptive study.Place and Duration of study: Fauji Foundation Hospital, Rawalpindi from Jan 2002 to Dec 2003.Patients and Method: Thirty diagnosed cases of early breast cancer in clinical stage I and II were included. Patients with solitary lump with size up to 4 cm in biggest diameter, 5 cm with large sized breasts and patients with lump in one breast were included. Patients with multicentric diseases, lump larger than 4 cm in size in greatest dimension, lump situated beneath areola, lumps fixed to skin or deeper structures were excluded.  Result: There were 2 (6.67%)  cases of seroma formation and 1 (3.33%) case of wound infection, 8 (26.67%)  patients suffered persistent painful shoulder movements and arm pain, 4 (13.33%) patients suffered breast disfigurement. 3 (10%) cases of loco-regional recurrence. 1 (3.33%) patient underwent mastectomy and 2 (6.66%) patients underwent further local excision,. Percentage of ductal carcinoma in post-menopausal women was also high. There was no mortality.Conclusion: Breast conservation surgery is equally effective as mastectomy in the treatment of early breast cancer as there is no statistically significant difference in disease-free survival and overall survival.